Performance Evaluation of Semi-quantitative Urine Albumin Creatinine Ratio Using Meditape UC-11A Strip Test - Elizabeth Sidhartha; Thoeng Ronald (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
The Urine Albumin/Creatinine Ratio (uACR) is one of the earliest markers of glomerular disorders. A comparative study of semi-quantitative urine uACR and quantitative uACR tests was carried out using Meditape UC-11A test strips on the Sysmex UC-3500 (automated urinalysis instrument) and Roche Cobas 501, respectively. A total of 213 retrospective data of urine chemistry tests were collected. Semi-quantitative urine albumin, creatinine, and uACR data were obtained using Meditape UC-11A strips on Sysmex UC-3500, whereas quantitative data were obtained using Roche Cobas c501. A weighted Cohen's Kappa agreement, sensitivity, specificity, PPV, NPV, and accuracy were analyzed using data from both instruments. The Kappa values for urine albumin, creatinine, and uACR between the semi-quantitative and quantitative methods were 0.83 (CI 0.771– 0.880), 0.535 (CI 0.417–0.652), and 0.691 (CI 0.606–0.775), respectively. The sensitivity, specificity, PPV, NPV, and accuracy of semi-quantitative methods were 90%, 73.3%, 75%, 89.2%, and 81.2%, respectively. The semi-quantitative uACR test on the UC-3500 showed excellent performance and could be used as a screening test for early detection of impaired kidney function.